STUDIES ON HAEMATO-BIOCHEMICAL INDICES IN JERSEY CROSSBRED CATTLE AFFECTED WITH RETENTION OF FETAL MEMBRANES - T. Sarath; A. Thangamani; R. Rajkumar; N. Arunmozhi; U.S. Kalyaan; G. Monica; S. Manokaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present investigation was conducted to study the changes in the haemato- biochemical indices in normally calved crossbred cows with retention of placenta (n=60) and dystocia with retention of placenta (n=25) and compared with normally calved crossbred cows without retention of placenta (n=10) during the period between July 2022 to December 2023. Result showed that marked leukocytosis, lymphopenia, neutrophilia and eosinophilia in retention of fetal membrane (RFM) affected cows. Serum biochemical indices revealed significant increase (p<0.05) in the concentration of enzymatic parameters (aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase), decreased mineral parameters (calcium and phosphorus) and metabolic parameters in RFM affected cows. In conclusion, enzymatic, mineral and metabolic parameters can be used as biochemical indicators for the prediction of RFM in Jersey crossbred cows.